2021
DOI: 10.3390/ijerph18136819
|View full text |Cite
|
Sign up to set email alerts
|

Review of Workplace Based Aerosol Sampler Comparison Studies, 2004–2020

Abstract: We provide a narrative review on published peer-reviewed scientific literature reporting comparisons of personal samplers in workplace settings published between 2004 and 2020. Search terms were developed for Web of Science and PubMed bibliographic databases. The retrieved studies were then screened for relevance, with those studies meeting the inclusion criteria being taken forward to data extraction (22 studies). The inhalable fraction was the most common fraction assessed with the IOM sampler being the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…There are challenges in comparing exposure datasets because different designs of personal samplers can possess different sampling efficiencies. A review (54 references) of studies published between 2004 and 2020 compared 8 different samplers but, alas, found no discernible trends. The authors recommended that a standardised testing protocol be adopted to aid future comparisons.…”
Section: Air Analysismentioning
confidence: 98%
“…There are challenges in comparing exposure datasets because different designs of personal samplers can possess different sampling efficiencies. A review (54 references) of studies published between 2004 and 2020 compared 8 different samplers but, alas, found no discernible trends. The authors recommended that a standardised testing protocol be adopted to aid future comparisons.…”
Section: Air Analysismentioning
confidence: 98%
“…The SKC Aluminium cyclone (flow rate of 2.5 L/min) was also assessed. It is also worth noting for this article that the authors also performed field measurements which are discussed in our workplace sampler comparison review (Hanlon et al, 2021) [13]. Samplers were compared to each other and not to an inhalable convention and the authors concluded that the IOM sampler had the lowest coefficient of variation (i.e., the best precision) of the samplers and was least affected by wind speed changes (wind speeds of 0, 0.2 and 1.0 m/s for the sampled dusts).…”
Section: Agricultural Dustsmentioning
confidence: 99%
“…A recent survey of aerosol sampling heads used within the metals industry revealed a wide variety of inhalable, thoracic, and respirable samplers as being commonly used [13] ( Hanlon et al, 2021). This is not surprising given that a wide variety of personal samplers that have been developed [14,15].…”
mentioning
confidence: 99%
See 1 more Smart Citation